Influence of parameters of digital conversion signal fluctuations in the amplitude-frequency characteristics of signals shift - Філоненко, С.Ф.; Косицька, Т.М. (Proceedings of National Aviation University (archive), 2009)
The results of experimental researches of influencing a sampling interval of acceleration and speed oscillation signals on amplitude-frequency relations of displacement signals after using the operations of double or unary transformation are reviewed. Are shown the main regularity a change of displacement signals output amplitudes from frequency of input signals at set values of a sampling interval. Is determined, that the sampling interval does not influence on amplitude-frequency displacement signals relations under condition, that the transformation is executed from time constants, which value is peer to half part of period a input oscillation signals of speed and acceleration.